Emerging Therapies in Hemophilia: Improving Equitable Access to Care - Lewandowska M; Nasr S; Shapiro AD (Journal of Blood Medicine)
Magdalena Lewandowska,1 Sonia Nasr,2 Amy D Shapiro1 1Indiana Hemophilia & Thrombosis Center, Inc., Indianapolis, Indiana, USA; 2GLOVAL LLC, Broomfield, Colorado, USACorrespondence: Amy D Shapiro, MD. Indiana Hemophilia and Thrombosis Center, Inc., 8326 Naab Road, Indianapolis, IN, 46260, USA, Email ashapiro@ihtc.orgAbstract: In recent years, gene therapy and bio-engineered hemostatic molecules have revolutionized treatment for people with hemophilia. These innovative therapies aim to decrease treatment burden and improve patient quality of life. Additional novel therapies, including next-generation mimetics and agents that rebalance hemostasis, are currently being evaluated in clinical trials. Technological advances such as point-of-care musculoskeletal ultrasound and artificial intelligence may improve patient diagnostic and treatment outcomes. However, for the majority of patients with hemophilia worldwide, diagnosis and effective treatment are inaccessible. Achieving health equity for all hemophilia patients requires improved identification of barriers to optimal care, including socioeconomic status, race/ethnicity, gender, disease severity, inhibitor status, age, and use of Hemophilia Treatment Centers. Access to novel hemophilia therapies should be ensured for all patients. Approaches to improving equity include a decision-making partnership between the patient and clinician, stakeholder engagement, and pharmaceutical industry support. The development of novel hemophilia therapies should be leveraged with a patient-centered care approach to improve health equity for all patients.Keywords: gene therapy, non-factor therapy, artificial intelligence, point-of-care musculoskeletal ultrasound, health equity